Kondycja współczesnego człowieka - Głowiak, Daria (Studia Edukacyjne, 2025)
The modern world is characterized by its ability to change rapidly, its uncontrollable range of global transformations, socio-cultural shifts, the development of technology, the decline of communal values, pluralization of cultures, and multiple other factors with a significant impact on the individual’s life. The variety, intensity, scope, and rapidity of the changes that the world goes through exposes the physical and mental condition of the contemporary human being to a myriad negative influences and consequences. The number of external stimuli that a person encounters in the real and digital worlds has made fear and anxiety parts of human life. The above circumstances explain why the general condition of humans has been changing along with the changing world. The article addresses aspects that constitute this condition. The modern human and the broadly understood modern society are characterized first and foremost by a focus on individual aspirations, distancing oneself from communal values, consumerism, as well as newly emerging forms of spirituality aiming at finding the way to one’s inner self and personal development. In the source literature regarding the aspects of the contemporary human condition, premises often emerge about the modern individual’s pursuit to improve themselves physically, stemming from the necessity of integrating such subjects as technology or unconventional medicine. Methods: This is an overview of elements of the condition of temporary human beings based on available literature. The article aims to highlight the essential operation of modern society. Results: All the goals of a modern human being are a direct response to what they perceive in their contemporary environs: a world filled with military conflict, the pursuit of the market values, an endless information flow, cultural interpenetration, and undermining all the moral patterns known to humanity until the present.